O mandamento do sábado no Decálogo: um estudo exegético de Ex 20,8-11; Dt 5,12-15 - Alves, Paulo Antônio (2015)
The content of this dissertation is a reading of the Sabbath commandment in the two versions of the Decalogue, Ex 20,8-11 and Dt 5,12-15. This reading indicates some features provided by the biblical text, while a structure of the sabbath commandment and also offers some contributions of the Rabbinical Tradition and Christian theologians on this central theme, so deep and wide. Ex 20,8-11 is a positive formulation, one apodictic law, a law / teaching. It does not impose a cultural practices, but a rest, which should be consecrated to God. As in Gn 2,1-4a, the rest of the seventh day is explained as a limit set by God with his creative power. As the Temple delimited space, the same does the sabbath, delimiting a while and consecrates to God. Motivation is strictly theological: commemorates the creation and divine rest of the seventh day: a liberation from nothing, which is in its end a holy / time spent as separate and blessed because fruitful, full of life. These motivations are different, but both part of the same project: give to Israel through the command / law / teaching of the Sabbath a place of identity lived in a separate time: the seventh day. Dt 5,12-15 is justified by one anthropological motivation, social and equal, which extends even to nature: the animals and the land: it makes memory of the liberation of the land of Egypt by God's action. Besides these two important theological concepts, Creation and Liberation, the Sabbath commandment conveys the concepts of holiness, earth, chosen people and the verb keep, remember is to make an actualized memory. The sabbath commandment is updated by both schools to redefine and justify Israel's identity in the light of the central event for its history; the liberation of the land of Egypt. In addition to support the identity, the sabbath commandment is constituted as a source of spiritual nourishment for Israel and the Church, through the theology of compliance and not break or replacement. It commandment was structured as a centre of the Decalogue, in its two versions, also having a centre granting it a status: hermeneutical key of the Torah, the heart of the Alliance and subsequent laws